Case report: Precise NGS and combined bevacizumab promote durable response in ALK-positive lung adenocarcinoma with multiple-line ALK-TKI resistance - Xiong, Jin; Xia, Lei (Frontiers in Oncology, 2024)
Liquid biopsies including pleural fluid or plasma are commonly applied for patients with advanced non-small cell lung cancer (NSCLC) and pleural effusion (PE) to guide the treatment. ALK-TKIs are the first options for patients with ALK-positive mutations and combining ALK-TKIs with angiogenic agents may improve survival. We report here one case with ALK-positive lung adenocarcinoma in which the patient achieved a prolonged progression-free survival (PFS) of 97 months after undergoing precise pleural effusion NGS and receiving combined bevacizumab treatment following multiple-line ALK-TKI resistance.